LAJU PERUBAHAN KADAR AIR, KADAR PROTEIN DAN UJI ORGANOLEPTIK IKAN LELE ASIN MENGGUNAKAN ALAT PENGERING KABINET (CABINET DRYER) DENGAN SUHU TERKONTROL - Yuarni, Desi; Kadirman, Kadirman; Jamaluddin P, Jamaluddin P (Jurnal Pendidikan Teknologi Pertanian, 2015)
Fishing isone of thepotential protein sectorsof Indonesian society. Fishery productsis easilydamagedbecause they have high water content, it make a suitableplaceforbreedingof microorganismsandspoilage bacteria, so it is necessaryto do processing, one of which isprocessed intosalted fish. The purpose of this study was to determine the rate of change in water content, protein content, and organoleptic test catfish by drying using a cabinet dryer with controlled temperature. This study uses acompletely randomized design, which consists ofa singlefactorthat islongerdrying8, 10, 12hours. Data analysis of variance(ANOVA) followed bya further testDMRT. The results showedthat thedrying timesignificantly affected themoisture contentchanges, protein content, andorganoleptic test. Based on the test results, fishery that treatment drying time of 8 hours has a 30,22% moisture content, 48,68% protein content, 10 hours drying time has a 26,62% moisture content, 51,20% protein content, drying time 12 hours had higher levels 19,64% of moisture content, and 55,00% protein content, the organoleptik characteristics and treatments that have the highest level of preference in terms of appearance and odor treatment contained in the drying time of 8 hours, and to sense are in treatment 12 hours drying time, drying time treatment 10 hours is a treatment that has the characteristics and preference level of the highest rated in terms of the texture of salted catfish produced